Pembuatan Kebijakan dan Perencanaan Pendidikan Pada Sekolah SMKN 1 Percut Sei Tuan - Fatih, Muhammad Al; Amiruddin, Amiruddin (Peneliti.net, 2025)
Education policy is a set of rules as a form of partiality from the government in an effort to build an education system in accordance with the goals and ideals that are mutually desired. This partiality concerns the context of politics, budget, empowerment, regulations, and so on. Educational strategy policy steps that are explained from the educational vision and mission in order to realize the achievement of educational goals in a society for a certain period of time. This research aims to describe policy making and educational planning at SMKN 1 Percut Sei Tuan. Meanwhile, educational planning is a series of processes that are prepared to face the future so that educational goals can be realized effectively and efficiently. The aim of this research is to use a qualitative case study method approach which is used to obtain information on how to make educational policies and plans at SMKN 1 Percut Sei Tuan.